Visual texture agnosia influences object identification in dementia with Lewy bodies and Alzheimer's disease. (August 2020) - Oishi, Yuka; Imamura, Toru; Shimomura, Tatsuo; Suzuki, Kyoko
Abstract: Background: Numerous studies have shown visuoperceptual/visuospatial deficits in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD). Visual texture recognition is also impaired in patients with DLB and AD. Although patients with DLB often exhibit visual misidentifications of objects, there are few studies on the relationships between visual texture recognition and viewpoints for object recognition. Objectives: The aim of this study was to clarify how viewpoints, textures, and visual cognitive functions affect object recognition and result in visual misidentifications in patients with DLB or AD. Methods: A total of 37 patients with probable DLB and 58 with probable AD and 32 age-matched healthy controls underwent neuropsychological and visuoperceptual assessments, and performed object identification tasks under four conditions (non-canonical view + blurry texture, non-canonical view + clear texture, canonical view + blurry texture, canonical view + clear texture). The relationship between object identification and other visuoperceptual functions was analyzed. Results: Patients with DLB and AD exhibited significantly impaired object recognition under non-canonical viewing with blurry texture conditions, with the DLB patients exhibiting a significantly worse performance than the AD patients. Patients with DLB and AD exhibited visual misidentifications during object identification tasks under non-canonical viewing. In patients with DLB, the number of visual misidentifications was significantly correlated with the scores of visual texture recognition. Conclusions: The present study showed that significantly impaired object recognition in patients with DLB under the influences by both viewpoint and visual texture and in those with AD under the influence by viewpoint. Visual misidentification in object recognition could be associated with impaired visual texture recognition in DLB.